Addressing non-tariff measures in ASEAN - Gloria O. Pasadilla (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2013)
Intra-ASEAN trade has increased six-fold since 1993 but greater integration challenge looms in addressing non-tariff measures. The paper discusses the various ASEAN work programs on NTMs and assesses the incidence of Members' NTMs on various products. Various ways of accelerating the reduction of non-tariff barriers are discussed, including dispute settlement mechanisms. The paper highlights the importance of a unilateral approach in addressing NTMs and the use of regulatory impact analysis to improve policy making.
Keywords: F1; 330; ASEAN; Trade; Non-tariff; Mutual Recognition; Conformity Assessment; SPS; TBT